PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP KEBIJAKAN HUTANG PADA PT XYZ YANG BERGERAK DIBIDANG LOGISTIK DAN PENYEWAAN ALAT BERAT - Putri Lestari; Wasti Reviandani (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This study aims to determine the effect of liquidity and profitability on debt policy at PT XYZ which is engaged in logstiks and heavy equipment rental. This research is a quantitative research. The population in this study is all the financial statements of PT XYZ in 2016-2020, while the samples used in this study are the income statement and balance sheet statements in 2016-2020. The technique of data collection is done with the documentation technique. The data analysis technique used is multiple linear regression. The results of this study indicate that liquidity (Current Ratio) and profitability (Return on Assets) have no significant effect on debt policy simultaneously affect debt policy. If assets have increased, it will affect the use of debt to finance company assets.